2020
DOI: 10.3390/jlpea10010005
|View full text |Cite
|
Sign up to set email alerts
|

High-Efficiency Switched-Capacitor DC-DC Converter with Three Decades of Load Current Range Using Adaptively-Biased PFM

Abstract: A fully-integrated switched-capacitor (SC) DC-DC converter that steps down 2.0 V to 0.9 V with a peak efficiency of 80% is implemented in a 0.18 μ m CMOS process. An ultra-low-power voltage-controlled oscillator that generates a wide range of switching frequencies is proposed to extend battery runtime. An efficiency >70% for load currents in the range of 12 μ A to 17.8 mA is achieved by implementing a novel adaptively-biased pulse frequency modulation (ABPFM) technique in the controller. A symmetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…The paper [10] presented a modulation method to enhance the efficiency of a SCC operates to supply portable electronic devices assuming a wide range of load variation. It has been shown that decreasing the pulses frequency at light loading cuts the frequency-dependent losses and there-…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…The paper [10] presented a modulation method to enhance the efficiency of a SCC operates to supply portable electronic devices assuming a wide range of load variation. It has been shown that decreasing the pulses frequency at light loading cuts the frequency-dependent losses and there-…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…Voltage regulation of an SCC can be achieved by frequency control [10]. Reducing the switching frequency allows the capacitors voltage to drop and accordingly decreases the output voltage.…”
Section: Object and Hypothesis Of The Studymentioning
confidence: 99%
“…The output voltage of an SCC can be attenuated from the maximum no-load voltage by adjusting the switching frequency or by modulating blanking intervals [18], [19]. The nominal efficiency of the SCC is equal to the ratio of the regulated to no-load voltages (Vo/Vo,OC).…”
Section: Introductionmentioning
confidence: 99%
“…Restriction of power consumption on the application core circuitry can compromise the performance of system. The use of high-efficiency DC-DC converters increases the runtime, and the use of fully-integrated converters, such as switched-capacitor converters, further helps to reduce the overall solution size [3]. Additionally, increasing the switching frequency of the DC-DC converter reduces the size of the energy element such as the inductor or capacitor [4].…”
Section: Introductionmentioning
confidence: 99%